2021
DOI: 10.3390/su131911015
|View full text |Cite
|
Sign up to set email alerts
|

Dissatisfaction Responses of Tourists in the Havana World Heritage Site

Abstract: This paper aims to assess the relationships between tourists’ negative evaluation of key management areas in the cultural city, their overall satisfaction and future intentions. More specifically, this paper proposes a covariance-based structural equations model (CB-SEM) to assess the influence of tourists’ dissatisfaction caused by failures in tourist and cultural services, hygiene and infrastructure on their overall satisfaction with the cultural trip and their intentions to repeat it. Using data collected f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 37 publications
(86 reference statements)
0
3
0
Order By: Relevance
“…The level of visit frequency helps researchers to identify different travel behaviors regarding destination choices, travel experience, and satisfaction [7,34,74]. Previous research indicated that the proportion of repeat visitors was greater than that of first-time visitors; thus, managing destination reputation and promoting a positive destination image for repeated, committed, and loyal visitors is important [26,33,[79][80][81]. This study explores WHS visits and past experience among inbound travelers who visit WHSs in Uzbekistan.…”
Section: Past Experience and Whss In Uzbekistanmentioning
confidence: 99%
“…The level of visit frequency helps researchers to identify different travel behaviors regarding destination choices, travel experience, and satisfaction [7,34,74]. Previous research indicated that the proportion of repeat visitors was greater than that of first-time visitors; thus, managing destination reputation and promoting a positive destination image for repeated, committed, and loyal visitors is important [26,33,[79][80][81]. This study explores WHS visits and past experience among inbound travelers who visit WHSs in Uzbekistan.…”
Section: Past Experience and Whss In Uzbekistanmentioning
confidence: 99%
“…This outcome re-enforces the important role of hygiene and safety that may prevail in the formation of a non-positive or negative overall experience of visitors. In more detail, the absenteeism of hygiene and safety measures may result in peoples' dissatisfaction and/or negative experiences, and this has being been heralded for decades by researchers within or outside the tourism field (Bianchi, 2016;Herzberg et al, 1959;Lam--González et al, 2021). Yet, rather surprisingly, the absence of high scores of these particular aspects in models 1 to 3 (as presented previously), may not yield high scores of the outcome (i.e.…”
Section: Complex Solutionsmentioning
confidence: 87%
“…These include, hygiene and safety aspects (Alrawadieh et al, 2019;Kaushal & Srivastava, 2021;Xie et al, 2021), marketing dynamics (Mossberg, 2007;Pappas, 2019), quality (Suhartanto, 2020;Lee et al, 2011), price issues (Pappas, 2019;Campo & Yagüe, 2009), and social aspects (Christou & Sharpley, 2019;Lin et al, 2019;Zatori et al, 2018). Nonetheless, these same key factors may result in the non-positive or negative experience of tourists (Bianchi, 2016;Lam--González et al, 2021). For instance, the study of Christou et al (2018) revealed that various factors, such as lack of quality, hygiene and safety issues, unrealistic expectations as a result of false marketing, as well as over-priced offerings may be the cause of negative tourist emotions.…”
Section: Complexity Theory and Complexity In The Night Experiential E...mentioning
confidence: 99%